3‐D Subsurface Geophysical Modeling of the Charity Shoal Structure: A Probable Late Proterozoic‐Early Paleozoic Simple Impact Structure in Eastern Lake Ontario - Mary H. Armour; Joseph I. Boyce; Phillip Suttak; Doug Hrvoic (Earth and Space Science)
Abstract The Charity Shoal structure is a circular, ∼1.2‐km‐diameter, bedrock‐rimmed shoal in eastern Lake Ontario with a ∼20‐m‐deep central basin. The structure has been proposed as a possible Middle Ordovician impact crater or volcanic intrusion. We conducted marine seismic and magnetic surveys (9‐km2) and 3‐D geophysical modeling to better resolve the Charity Shoal subsurface geology and possible origins. Three models were evaluated: (a) a buried (>450 m) impact structure in Mesoproterozoic basement, (b) a maar‐diatreme, (c) a cylindrical, zoned volcanic plug. Seismic profiles and multi‐beam bathymetry revealed >30 m of Quaternary sediments overlying Middle Ordovician (Trenton Group) carbonate bedrock and complex, 3‐dimensional folding and faulting of the structure rim. Magnetic surveys recorded an annular magnetic high (>600 nT) over the structure rim and a central magnetic low (∼500–600 nT) coincident with a ∼−1.7 mGal Bouguer gravity anomaly. The continuity of Trenton Group strata in seismic profiles rules out a previously proposed Mesozoic maar‐diatreme intruded into Paleozoic strata. The zoned volcanic plug model reproduced the annular magnetic anomaly but was incompatible with Bouguer gravity profiles. The magnetic anomaly was best reproduced by a simple impact structure seated in Mesoproterozoic basement at 450–500 m depth with a rim‐to‐rim diameter of ∼1.2 km and rim height of ∼10–20 m. A 100‐m wide and 50‐m‐deep channel in the Mesoproterozoic basement may record fluvial dissection of the southwestern rim. A buried (>450 m), simple impact crater is most compatible with all available geophysical data at Charity Shoal.